2019
DOI: 10.1080/02688697.2019.1698011
|View full text |Cite
|
Sign up to set email alerts
|

Does preoperative health-related quality of life predict survival in high-grade glioma patients? – a prospective study

Abstract: Purpose: To explore if preoperative patient-reported health-related quality of life (HRQoL) provides additional prognostic value as a supplement to other preoperatively known clinical factors in patients with high-grade glioma (HGG). Methods: In a prospective explorative study, 114 patients with high-grade glioma were included. The participants completed the generic HRQoL questionnaire EQ-5D 3L, and the disease-specific questionnaires EORTC QLQ-C30 and EORTC QLQ-BN20 1-3 days before surgery. Operating neurosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Studies have concluded that assessment of these patient-reported outcomes (PROs) is more accurate than external measurement by physicians or other health professionals [8]. The prognostic implications of HRQoL data have been widely reported for colorectal cancer [4,5,[9][10][11] and other cancer entities, including head and neck [12], breast [13][14][15], and brain [16]. Standard therapy for rectal carcinoma includes neoadjuvant radiochemotherapy [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have concluded that assessment of these patient-reported outcomes (PROs) is more accurate than external measurement by physicians or other health professionals [8]. The prognostic implications of HRQoL data have been widely reported for colorectal cancer [4,5,[9][10][11] and other cancer entities, including head and neck [12], breast [13][14][15], and brain [16]. Standard therapy for rectal carcinoma includes neoadjuvant radiochemotherapy [17,18].…”
Section: Introductionmentioning
confidence: 99%